Moderating the Criminal Thinking–Delinquency Relationship with a Free Market Cultural Ethos: Integrating Micro- and Macro-Level Concepts in Criminology - Walters, Glenn D. (European journal on criminal policy and research, 2023)
The current study tested the interaction between micro- and macro-level criminological concepts to determine whether a free market cultural ethos moderated the criminal thinking-delinquency connection. Using a cross-national sample of 65,923 youth (32,614 boys, 33,309 girls, 10 to 20 years of age), the link between criminal thinking and delinquency was explored in 28 nations, each of which had been scored on the Heritage Foundation’s Index of Economic Freedom. Results revealed that a free market cultural ethos had a significant moderating effect on the criminal thinking-delinquency relationship. These results suggest that macro-level free market attitudes toward personal wealth as a cultural goal may interact with such micro-level criminological concepts as criminal thinking and delinquency to alter important criminological associations.